(untitled) (Global Journal of Human-Social Science, 2023)
This study is the result of design work on concrete tanks that include built-in grids with aquatic plants that help in the natural feeding of fish species The model was elaborated from an optimal solution directed by the authors in the orientation of group studies The realization of a will for the execution and construction of concrete tanks school tank for the production of fish at the Faculty of Veterinary Medicine of Huambo